Efect of load distribution on longitudinal and lateral forces acting on each wheel of a compact electric vehicle - Kunjunni, Baarath; Muhammad Aizzat, Zakaria; Anwar, P. P. Abdul Majeed; Ahmad Fakhri, Ab Nasir; Mohamad Heerwan, Peeie; Umar Zakir, Abdul Hamid (Springer Nature Switzerland, 2020)
Autonomous vehicle is gaining popularity in the market worldwide. Most autonomous vehicle are based on electric vehicles since they are easy to control. The torque control of electric vehicles is precise and easy since electric motor torque can be manipulated by controlling the motor current. Furthermore, the load of the vehicle afects the motor torque of an electric vehicle. A higher vehicle load requires high motor torque to propel the vehicle. Often in autonomous vehicle, the vehicle parameters and stability measure are set within a limit based on standard vehicle settings. However, a vehicle loaded with extra mass on either side can ofset these parameters afecting the efciency of the controller. Thus, in this paper the efect of load on vehicle longitudinal and lateral forces is identifed. A simulation model of a two rear in-wheel motored electric vehicle is developed. The model is used to analyze the efect of load on vehicle longitudinal and lateral forces. Based on the result, increasing the load on the side of direction of lateral motion increases the lateral force generated. The high lateral force causes the tires to approach the tire friction circle limit. This can afect the automated vehicle performance since the tires are in unstable region.